HUBUNGAN KONSEP DIRI DENGAN PERILAKU KONSUMTIF PADA REMAJA Dl SMK KESEHATAN - Fitriani & Muslimah Zahro Romas (LPPM Universitas Proklamasi 45, 2014)
Forty adolescence students participated in this research. They are from a health vocational school. During their school time they stay in a rent house / boarding house, since their parents live in other islands. Objective of this research is to verify the relationship between adolescence's consumptive behavior and their self-concept. It is expected that this result research will enrich parents and guidance counselor teacher in monitoring their grow-up children. Hypothesis of this research is that there is negative relationship between adolescence's self-concept and their consumptive behavior. The stronger their selfconcept, their consumptive behavior will be less likely manifest. On the other hand, the more vulnerable their self-concept, the consumptive behavior will be more likely manifest. Result of this research revealed that the Pearson coefficient correlation rxy = -0.673, p<0.05. It means that the research hypothesis is verified. However there are still three research limitations which relate to the respondent's characteristics. Several suggestions for the next research are discussed.